Stem cells and regeneration in plants - Sena,G (Nephron Experimental Nephrology, 2014)
Background: Plants are characterized by indeterminate post-embryonic development that is evident, for example, in the continuous branching of shoots and roots. High competence to regenerate tissues is another consequence of such intrinsic developmental plasticity in plants. It has been suggested that specialized groups of cells within plant meristems should be compared to stem cells in animals, but the utility of this label in the context of post-embryonic plant development and regeneration is often debated. Summary: This paper is organized into 3 short sections, where (a) key observations and experimental results on tissue regeneration in plants - mainly in the model system Arabidopsis thaliana, (b) stem cell activity and (c) their role in regeneration are described. The main focus is maintained on the critical aspects of defining stem cell-ness in plants, particularly in the context of tissue regeneration. A number of recent excellent reviews are cited throughout the text to give the reader the appropriate tools to dig deeper into the various stimulating topics introduced here. Key Messages: Despite the remarkable somatic developmental plasticity characterizing post-embryonic development in plants, use of the classic concept of stem cells has been imported from the animal literature with the goal of facilitating our understanding and description of plant developmental processes. It is not clear if this is the case, especially in light of the recent experimental results on root regeneration in Arabidopsis mutants.